An EM Modeling for Rescue System Design of Buried People. (24th June 2015) - De Leo, A.; Petrini, V.; Russo, P.; Scalise, L.; Di Mattia, V.; Primiani, Valter Mariani; Cerri, G.
Abstract : The development of a rescue system for buried persons is a subject of growing importance in case of occurrence of natural disasters such as earthquake, landslides, or avalanches. In this paper a fully analytical model has been developed to get some fundamental a priori design characteristics. The proposed system is based on the detection of the victim movements due to its respiratory activity: in particular, when an electromagnetic (EM) wave impinges on a human body, the analysis of the reflected wave parameters such as amplitude, frequency, phase, or delay time allows for the detection of the breathing frequency. The model is simple on purpose because the great uncertainty concerning the characterization of many environmental parameters of a general situation makes a very detailed model useless. However, it is accurate enough to provide useful information about system design, filling the gap in the literature concerning the electromagnetic formulation of such kinds of problems. A system prototype was built using laboratory equipment to experimentally validate the model, and subsequently breathing frequency measurements were carried on, both in a lossless laboratory environment and in a lossy realistic scenario.